Clinical and Magnetic Resonance Imaging Outcome Predictors in Pediatric Anti–N‐Methyl‐D‐Aspartate Receptor Encephalitis. Issue 1 (29th May 2020) - Bartels, Frederik; Krohn, Stephan; Nikolaus, Marc; Johannsen, Jessika; Wickström, Ronny; Schimmel, Mareike; Häusler, Martin; Berger, Andrea; Breu, Markus; Blankenburg, Markus; Stoffels, Johannes; Hendricks, Oliver; et al.
Abstract : Objective: To evaluate disease symptoms, and clinical and magnetic resonance imaging (MRI) findings and to perform longitudinal volumetric MRI analyses in a European multicenter cohort of pediatric anti–N‐methyl‐D‐aspartate receptor encephalitis (NMDARE) patients. Methods: We studied 38 children with NMDARE (median age = 12.9 years, range =1–18) and a total of 82 MRI scans for volumetric MRI analyses compared to matched healthy controls. Mixed‐effect models and brain volume z scores were applied to estimate longitudinal brain volume development. Ordinal logistic regression and ordinal mixed models were used to predict disease outcome and severity. Results: Initial MRI scans showed abnormal findings in 15 of 38 (39.5%) patients, mostly white matter T2/fluid‐attenuated inversion recovery hyperintensities. Volumetric MRI analyses revealed reductions of whole brain and gray matter as well as hippocampal and basal ganglia volumes in NMDARE children. Longitudinal mixed‐effect models and z score transformation showed failure of age‐expected brain growth in patients. Importantly, patients with abnormal MRI findings at onset were more likely to have poor outcome (Pediatric Cerebral Performance Category score > 1, incidence rate ratio = 3.50, 95% confidence interval [CI] = 1.31–9.31, p = 0.012) compared to patients with normal MRI. Ordinal logistic regression models corrected for time from onset confirmed abnormal MRI at onset (odds ratio [OR] = 9.90, 95% CI = 2.51–17.28, p = 0.009), a presentation with sensorimotor deficits (OR = 13.71, 95% CI = 2.68–24.73, p = 0.015), and a treatment delay > 4 weeks (OR = 5.15, 95% CI = 0.47–9.82, p = 0.031) as independent predictors of poor clinical outcome. Interpretation: Children with NMDARE exhibit significant brain volume loss and failure of age‐expected brain growth. Abnormal MRI findings, a clinical presentation with sensorimotor deficits, and a treatment delay > 4 weeks are associated with worse clinical outcome. These characteristics represent promising prognostic biomarkers in pediatric NMDARE. ANN NEUROL 2020 ANN NEUROL 2020;88:148–159